GUIDELINES FOR SUSTAINABLE WASTE MANAGEMENT OF THASALA SCHOOL, CHIANGMAI PROVINCE - Jinakot, Thanakorn; Pornwieng , Suban; Manokarn, Monnapat (Journal of Buddhist Education and Research (JBER), 2024)
This study aims to: (1) Study the current state of waste management at Thasala School, Chiang Mai Province. (2) Develop practical guidelines for sustainable waste management. And (3) Evaluate the effectiveness of the implemented sustainable waste management practices. The target groups for the study include: There were 2 educational administrators, 5 educational institution administrators, 10 educational supervisors, 12 academic teachers, and parent 142a total of 172 people. The results of this study found that 1) The overall waste management condition at Thasala School was found to be moderate. When considering each aspect of waste management practices, reuse ranked highest, followed by reduction and recycling, respectively. (2) A total of 30 approaches were categorized into three main areas: reuse, reduce and recycle. These guidelines are grounded in principles of economic sufficiency and utilize the Deming Cycle (PDCA) for further improvement. And (3) The evaluation confirmed that the developed guidelines were suitable, feasible, and beneficial for implementation